Toxicity and Antioxidant Activities of Indonesian Rambutan (Nephelium lappaceum L.) Peel Extracts: A Comparative Analysis Across Varieties Based on Phytochemical Content - Adzkia Failasufa; Irmanida Batubara; Bambang Pontjo Priosoeryanto; Auliya Ilmiawati (Jurnal Kimia Sains dan Aplikasi, 2025)
Indonesia has long been known as a tropical country rich in various local cultivars of rambutan (Nephelium lappaceum L.), including Aceh Lebak (AL), Aceh Pelat (AP), Binjai (B), Gula Batu (GB), and Sikoneng (SK). Due to their phenolic and flavonoid compound, rambutan peel extracts have been reported to exhibit antioxidant and antiproliferative properties. Variation among cultivars suggests potential differences in bioactive compound content and biological activity. The objective of this study was to evaluate the antioxidant and toxicity profiles of five rambutan peel varieties and their correlation with total phenolic compound (TPC) and total flavonoid content (TFC). The antioxidant activity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method, and phenolic and flavonoid contents were measured by colorimetric assays. Toxicity was assessed using the Brine Shrimp Lethality Test (BSLT). Bioautography analysis using TLC-DPPH was conducted to identify antioxidant-active compounds. In this study, all rambutan peel extracts indicated the presence of flavonoids, phenolics, saponins, steroids, alkaloids, and triterpenoids. The highest extract yield was observed in Sikoneng, also with the highest TPC and TFC values. The Binjai variety exhibited strong antioxidant activity (IC50 = 4.73 ± 0.19 mg/L) and three active antioxidant spots; however, it also exhibited toxicity (LC50 = 136.27 ± 6.58 mg/L). The correlation between total phenolic or flavonoid content and the observed biological activity was not statistically significant, indicating that additional metabolites or synergistic interactions may also contribute. These findings underscore the significant impact of biodiversity on differences in compound levels and potential biological activities among rambutan peel varieties.